2022
DOI: 10.1186/s12885-022-09824-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of Japanese patients with small bowel adenocarcinoma using next-generation sequencing

Abstract: Background Small bowel adenocarcinomas (SBAs) are rare and there is little comprehensive data on SBA genomic alterations for Asian patients. This study aimed to profile genomic alterations of SBA in Japanese patients using targeted next-generation sequencing (NGS). Methods We examined 22 surgical resections from patients with primary SBA. SBA genomic alterations were analyzed by NGS. Mismatch repair (MMR) status was determined by immunohistochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Genetic profiles indicate that the mutation rates of KRAS, APC, and CTNNB1 are lower in gastric-type SBA, although these are more commonly observed in intestinal-type SBA, suggesting that the characteristics of intestinal-type SBA resembles those of colorectal cancer. 15 In contrast, gastric-type SBA had fewer mutations, with the exception of GNAS mutations, implying that its characteristics are distinguishable from those of colorectal cancer. It has been reported that gastric phenotype is inversely associated with Wnt-signaling abnormalities, which is consistent with our results.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Genetic profiles indicate that the mutation rates of KRAS, APC, and CTNNB1 are lower in gastric-type SBA, although these are more commonly observed in intestinal-type SBA, suggesting that the characteristics of intestinal-type SBA resembles those of colorectal cancer. 15 In contrast, gastric-type SBA had fewer mutations, with the exception of GNAS mutations, implying that its characteristics are distinguishable from those of colorectal cancer. It has been reported that gastric phenotype is inversely associated with Wnt-signaling abnormalities, which is consistent with our results.…”
Section: Discussionmentioning
confidence: 97%
“…DNA extraction, NGS, and mutation calling were performed as described previously. 15,28 In brief, ~10 ng of DNA per sample was amplified using multiplex polymerase chain reaction (PCR) with the Ion AmpliSeq Cancer Hotspot Panel v2 (Thermo Fisher Scientific), which was designed to amplify 207 amplicons covering the 2849 Catalogue of Somatic Mutations in Cancer (COSMIC; http://cancer.sanger.ac.uk/cosmic) mutations in hotspot regions for the 50 most commonly reported oncogenes and tumor suppressor genes. Pooled and barcoded libraries were clonally amplified on Ion Sphere particles using emulsion PCR with the Ion Chef system and Ion PGM HI-Q View Chef Kit (Thermo Fisher Scientific).…”
Section: Next-generation Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there have been several reports of genomic analysis using formalin‐fixed, paraffin‐embedded (FFPE) samples in comparison with adjacent organ carcinomas 7,8 . However, few studies have reported genomic analysis, including gene expression analysis, using fresh‐frozen samples 2,3,9 …”
Section: Introductionmentioning
confidence: 99%
“…7,8 However, few studies have reported genomic analysis, including gene expression analysis, using fresh-frozen samples. 2,3,9 PVC was included as a SIC in the 4th edition of the World Health Organization (WHO) classification of tumors of the digestive system. 10 It was reclassified as an independent disease from small intestine, gastric, colorectal, and bile duct carcinomas since 2019 in the 5th edition, similar to the Union for International Cancer Control (UICC) classification.…”
Section: Introductionmentioning
confidence: 99%